A Study of Complex Substructures in a Foothill Belt of North western Taiwan Using Two-Dimensional Gravity Multiple-Source Model Inversion - Chun-Yi Yu; Chieh-Hou Yang; Kenn-Ming Yang; Rong-Ching Cheng; Shiuh-Tsann Huang (Terrestrial, Atmospheric and Oceanic Sciences, 2009)

(untitled)
The goal of this paper is to improve the capability of gravity inversion assessment of complex structures using a multiple-source model as indicated by a study of a foothill belt of north western Taiwan. In this study, a gravity inversion computer program is applied based on research developed by Tsai, which contains a Marquardt inversion algorithm for mathematical calculations and incorporates constraints on geological parameters. The computed and modified geological parameters are transformed into coordinates. The response of a proper geological model is calculated using the Talwani technique.